Weight gain in preterm low birth weight infants with multisensory intervention - Modi, Krupal; Khandare, Shilpa; Palekar, Tushar J.; Gazbare, Preeti; Shah, Vidhi; Mehta, Tanpreet Kaur (International Journal of Contemporary Pediatrics, 2018)
Background: Birth weight is a significant determinant of newborn survival. In neonatal deaths, LBW is the underlying cause in 60-80% cases. This study was aimed to assess whether preterm infants receiving Multisensory intervention had more rapid weight gain compared to control group infants during NICU stay. Methods: Subjects for the study were preterm infants between 32 to 37 weeks of gestation age with birth weight between 1500 g to 2500 g and staying in NICU. Participants meeting inclusion criteria were randomly divided into either experimental group (n=15) or control group (n=15). The experimental group received Multisensory stimulation such as Auditory, Tactile, Visual and Vestibular stimulation for 10 consecutive days (15 min. /day) in NICU. Control group received routine NICU care. Weight was measured using an electronic weighing scale at day-1, day-5 and day-10 of intervention in both the groups and collected data was analysed. Results: The preterm infants of the experimental group had shown better growth than those in the control group with statistically significant differences (p<0.05) between the study and the control group at end of 10 days of intervention. Conclusions: From Analysed data, it is concluded that 5-day of Multisensory intervention could not elicit statistically significant improvement in weight gain, but 10 days intervention could elicit significant improvement. The result supports the use of multisensory intervention as a cost-effective therapy to promote growth.